(3QSGdI aj GLJeGY GdCeQ hGdfgis - (3ejQRG CHh GdbGSe cdGfJQs
(3ChdgG (B:s
(3Gdbhd ai GLJeGY GdCeQ hGdfgi hJhVjM GdeQGe ai cd ebOeI s
(3BNQgG (B:s
(3Pdc GdGeJfGY hGdhLhH eDcOG ddGNJHGQ GdPi gh TQW ai GdCaYGd s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(130) s
Keywords: (3GdadSaI hGdefWbs